2020
DOI: 10.3390/su12072589
|View full text |Cite
|
Sign up to set email alerts
|

Sales Control Systems and Salesperson Commitment: The Moderating Role of Behavior Uncertainty

Abstract: Although sales control has been identified by previous literature as an effective tool to promote salesperson commitment, unclear categorization of the focal variables makes existing findings confounding. This paper aims to provide more nuanced understanding about the relation between sales control systems and salesperson commitment by categorizing sales control into outcome control, activity control, and capability control. Moreover, we explore the moderating role of behavioral uncertainty, which includes sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…Output control (which is the most widely studied form of control both within and outside the sales literature) focuses on final performance. For example, in a typical output control scheme, the sales volume, income or quota achievement of a salesperson is tracked and used as the benchmark for measuring their success (Li et al, 2020;Malek et al, 2018;Evans et al, 2007). On the other hand, behavior or process control is broken down into capability and activity controls.…”
Section: Salesforce Control Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Output control (which is the most widely studied form of control both within and outside the sales literature) focuses on final performance. For example, in a typical output control scheme, the sales volume, income or quota achievement of a salesperson is tracked and used as the benchmark for measuring their success (Li et al, 2020;Malek et al, 2018;Evans et al, 2007). On the other hand, behavior or process control is broken down into capability and activity controls.…”
Section: Salesforce Control Systemsmentioning
confidence: 99%
“…For example, most of the recent research on salesforce control outcomes either concerns variables related to the selling firm (e.g. sales performance) (Zang et al, 2020) or salespersons (salesperson commitment) (Li et al, 2020). There seems to be a lack of study addressing how salesforce controls affect main consumer behavioral intentions (outcomes).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While BBCSs have been reported to generate positive outcomes, such as role clarity, organizational commitment, intrinsic motivation and trust in supervisors (Challagalla JSTP 32,3 and Shervani, 1996;Jaworski and Kohli, 1991;Oliver and Anderson, 1994;Ramaswami, 2002), they simultaneously stifle individuals' creativity, flexibility, innovation (Merchant, 1985) and risk-taking (Cravens et al, 1993;Oliver and Anderson, 1994). The organizational control literature suggests that BBCSs involve frequent performance evaluation and top-down enforcement of routine activities, which has a deleterious effect on managers' motivation and emotions in the workplace (Li et al, 2020). Building on this contention, we propose BBCSs as hindering job demands that weaken the positive effect of job crafting.…”
Section: Moderation Of Outcome-and Behavior-based Control System On T...mentioning
confidence: 99%
“…Previous studies have found that a behavior-based control system is positively associated with several employee outcomes, such as sales skills and motivation, job satisfaction, trust in supervisors, and behavior performance [ 40 ]. By contrast, outcome-based control systems are based on objective measures of the outcomes (i.e., a salesperson’s sales volume, revenue, or quota attainment) that are demanded by the firm, and salespersons are fully responsible for their accomplishment, with little monitoring of salespersons by management [ 41 ]. Under an outcome-based control system, salespersons tend to have substantial autonomy in performing their jobs (e.g., they may choose their own sales strategies) and are tightly evaluated and rewarded for positive outcomes, such as a high sales volume, market share, and profit contribution [ 38 ].…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%